Mapping Communication Strategies of the Interfaith Dialogue Forum in North Labuhan Batu for Strengthening Religious Moderation - Sihombing, Ibrahim; Kholil, Syukur; Yusnadi, Yusnadi (MUHARRIK: Jurnal Dakwah dan Sosial, 2023)
This study explores the practice of interfaith figure communication in efforts to build religious harmony among the community in North Labuhanbatu Regency. This research is a field study with a qualitative descriptive approach. Data were collected through direct observation, interviews, group discussions, and documentation. The subjects include religious figures, community leaders, and government officials in North Labuhanbatu Regency. Data analysis used the Miles and Huberman model, with stages of data reduction, display, and conclusion drawing/verification. The results show that interfaith communication among religious figures in Labuhanbatu Utara is based on Islamic principles that respect human values and build harmony. This communication is crucial for strengthening social interactions and achieving common goals in creating sustainable harmony. Religious figures in the FKUB (Forum Komunikasi Umat Beragama) of Labuhanbatu Utara play a role in preventing religious conflicts through dialogue and coordination with local government. Barriers to building harmony among religious communities in Labuhanbatu Utara include distorted information and fake news on social media. The role of the internet and social media has changed how people obtain religious information, making religious figures more involved in politics and facing various challenges.